The Non-Destructive Test Method as A Simple Way to Evaluate the Quality Of Metal Core Pcbs for High Power Micro-Assemblies - A.V. Sukhanov; A.I Artemova; R.S Litvinenko (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The article describes the necessity of an incoming quality control of the delivered power electronics elements especially at the stage of choosing a reliable supplier. In particular, in the field of the metal core PCBs production, there is a need to control not only its heat sink parameters, but also to control the quality of the joint interface of the metal core PCBs. Since the use of poor-quality materials or the violation of the technological process by the manufacturer can lead to the defects in the PCBs structure. Thus it can affect the heat sink efficiency and the reliability of the entire assembly. The article proposes and describes the method of nondestructive incoming quality control of metal core PCBs. This method is based on the use of ultrasonic layer-by-layer scanning for obtaining the internal structure of PCBs. The article presents the results of applying this method for the PCBs of various manufacturers. The data of the structure visualization and the influence of environment temperatures changes were also obtained. The result pictures of the tested samples before and after the thermal circling were obtained to study the possible degradation of the PCBs structure and its parameters.